Development of a Standardized Grading Scale for Atherosclerotic Disease of the Head and Neck. Issue 4 (July 2019) - Bonfante, Eliana; Calle, Susana; Solomon, Natalia; Jagolino, Amanda; Cai, Chunyan; Arevalo-Espejo, Octavio; Riascos, Roy; Sitton, Clark
Abstract : Objective: For research and risk factor analysis, a reproducible method quantifying atherosclerosis is necessary. Our aim was to develop a computed tomography (CT) angiography grading system to quantify atherosclerotic disease of the head and neck. Methods: Institutional review board–approved, retrospective analysis was performed on 152 patients who underwent head/neck CT angiography. A grading scale was designed to calculate plaque burden at multiple sites with the sum referred to as atherosclerosis score. Three radiologists calculated scores with an overlap of cases to calculate the intraclass correlation coefficient. Results: Without any prior training, the intraclass correlation coefficient between readers was considered fair. After a short tutorial, intraclass correlation coefficient was recalculated using separate patients, showing excellent correlation. Statistically significant positive correlation was found between atherosclerosis scale and age, hyperlipidemia, hypertension, and diabetes, but no correlation with sex or smoking status. Conclusions: A simple, visual grading scale for atherosclerosis in head/neck CT angiography was used to standardize reporting and better characterize a patient's risk of stroke.